2007
DOI: 10.1074/jbc.m704590200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of ATP-binding Cassette Transporter A1-mediated Cellular Lipid Efflux to Apolipoprotein A-I and Formation of High Density Lipoprotein Particles

Abstract: The ATP-binding cassette transporter A1 (ABCA1) plays a critical role in the biogenesis of high density lipoprotein (HDL) particles and in mediating cellular cholesterol efflux. The mechanism by which ABCA1 achieves these effects is not established, despite extensive investigation. Here, we present a model that explains the essential features, especially the effects of ABCA1 activity in inducing apolipoprotein (apo) A-I binding to cells and the compositions of the discoidal HDL particles that are produced. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
311
5
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(332 citation statements)
references
References 61 publications
(73 reference statements)
10
311
5
6
Order By: Relevance
“…This evidence is confirmed by reconstitution experiments, in which MsbA has been shown to translocate a wide variety of fluorescent-labeled phospholipids, albeit with low activity [72]. In the case of P-glycoprotein, studies in cell lines and reconstituted systems have suggested the involvement of this protein in transport of a variety of phospho-and glycolipids [65,70,[89][90][91]. However, this protein was first identified as the multidrug resistance transporter responsible for the inefficiency of long-term pharmacological treatments [92].…”
Section: Putative Catalytic Mechanism Of Abc Transporters Of the "Expmentioning
confidence: 55%
“…This evidence is confirmed by reconstitution experiments, in which MsbA has been shown to translocate a wide variety of fluorescent-labeled phospholipids, albeit with low activity [72]. In the case of P-glycoprotein, studies in cell lines and reconstituted systems have suggested the involvement of this protein in transport of a variety of phospho-and glycolipids [65,70,[89][90][91]. However, this protein was first identified as the multidrug resistance transporter responsible for the inefficiency of long-term pharmacological treatments [92].…”
Section: Putative Catalytic Mechanism Of Abc Transporters Of the "Expmentioning
confidence: 55%
“…64 The ability of ApoA1 to solubilize and bind lipids has a key role in formation of nascent HDL. 65 ApoA1/ABCA1-dependent generation of nascent HDL particles involves three stages. On the first stage, ApoA1 (lipid free or lipid bound) binds to ABCA1 that results in enhancing activity of the transporter in translocating phospholipids from the inner plasma membrane layer to the outer layer.…”
Section: Involvement Of Apoa1 In Cholesterol Esterificationmentioning
confidence: 99%
“…ApoA-I also plays key roles at various stages of RCT. It promotes efflux of cell cholesterol and phospholipids to HDL via the interactions with ATP-binding cassette transporter A1 (11); it provides a co-factor for lecithin:cholesterol acyltransferase (LCAT), which esterifies cholesterol and converts nascent discoidal to mature spherical HDL (2); it binds to the hepatic scavenger receptor and mediates selective uptake of HDL cholesterol esters by the liver (12).…”
mentioning
confidence: 99%